Oral disintegration films based on agar-agar with incorporation of hydroalcoholic extract of Hibiscus sabdariffa seeds - de Oliveira Dias, Jecielly; de Carvalho, Rosemary Aparecida; Nunes, Aline [UNESP]; Dos Santos Garcia, Rodrigo Henrique; de Menezes Rodrigues, Giovana; Yoshida, Cristiana Maria Pedroso; da Silva, Camila; Seiva, Fabio Rodrigues Ferreira [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Martelli, Silvia Maria; Garcia, Vitor Augusto Dos Santos [UNESP] (Elsevier, 2025)
This research aimed to produce and characterize agar-agar-based oral films by incorporating hydroalcoholic Hibiscus sabdariffa L. seeds (HES) extract. Four formulations were tested, varying the HES concentrations (1, 3, and 5 g/100 g of film-forming solution) with fixed concentrations of sorbitol and agar-agar. The oral films presented film-forming capacity and easy handling. No significant differences were observed in the mass (0.06 g) or thickness (0.06 mm) of the oral films, regardless of the HES amount added. The surface pH, with and without HES, remained around 6.9. The disintegration time was reduced by adding HES (83.25 and 70.78 s). The antioxidant properties were attributed to phenolic compounds (24.97 and 64.58 mg/100 g oral films) found in HES. The oral films showed hydrophilic characteristics (θ0 < 67°) at higher HES concentrations. Additionally, oral films with the addition of HES are considered sources of tryptophan. In vitro cytotoxicity tests confirmed that the films are safe for oral use. Therefore, oral films can be considered an innovative source for phenolic compound delivery, and their consumption would not irritate the oral mucosa nor are they considered serotonin precursors.